Analysis of the Influence of Governance Quality on the Performance of Savings and Credit Cooperatives in Togo - AVOGAN, Komlan (Archives of Business Research, 2022)
The objective of this paper is to analyze the influence of governance quality on the performance of savings and credit cooperatives in Togo. To do so, a governance quality index of fifty-five savings and credit cooperatives was calculated over the period from 2013 to 2019. The data was collected from the supervision unit of microfinance institutions and their managers. The results show that governance quality has a significant and positive effect on the financial performance of cooperatives. It positively influences the number of active borrowers and the percentage of female borrowers. However, it has a negative relationship with loan size. This paper presents the synthetic nature of governance quality in the Togolese context with a dynamic panel data model. It shows that improved governance has a positive impact on performance. It constitutes a tool for promoting good governance practices for the various actors involved in the microfinance sector and even a basis for developing a good governance charter for this sector.